ANALISIS KOHESI LEKSIKAL TERHADAP UNGKAPAN â€œEMANCIPATIONâ€ DALAM NOVEL THE HANDMAIDâ€™S TALE KARYA MARGARET ATWOOD - Khafifah, Siti Nur; Mirahayuni, N.K.; Garnida, Susie Chrismalia (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2016)
This paper discusses expressions of emancipation and lexical cohesion analysis of the expression of emancipation in Margaret Atwood’s The Handmaid’s Tale. The purpose of this research is to analyze the keywords and expression of emancipation that are used in the novel. The analysis is based on the theory of lexical cohesion (Halliday & Hasan, 1976). A descriptive qualitative approach is adopted, focusing on the keywords and expressions of emancipation. The study involves 86 data that contain the expressions of emancipation. The problems to be investigated in the study are: (1) What are the main keywords related to the idea of emancipation used in Margaret Atwood’s The Handmaid’ Tale?(2) What are the specific expressions related to the main keywords of the idea of emancipationused in Margaret Atwood’s The Handmaid’ Tale?, and (3) What kinds of lexical cohesion are shown between the idea of emancipation and the expresions of emancipation in Margareth Atwood’s The Handmaid’s Tale? The results of the study show the following points. The concept of emancipation can be analyzed into 5 keywords and each keyword is related to a number of other lexical items. The keywords are: 1) Gilead consisting 5 other lexical items; 2) Woman according to Margaret Atwood’ The Handmaid’s Tale consisting 25 other lexical items; 3) Red consisting 11 other lexical items; 4) Commander’s household consisting 5 other lexical items; and 5) Mayday consisting 4 other lexical items. This lexical cohesion analysis discusses each one of the keywords with the consideration of its context and events in the novel. The study also found various types of lexical cohesion used to present the idea of emancipation in the novel, including repetition, synonymy, antonymy, hyponymy. This research is expected to give some directions as to what lexical cohesion devices are worth analyzing. More studies maybe conducted in the same field with larger samples and more fictional text types, and with the use of lexical cohesion especially antonym, synonym, and hyponym. Keywords: lexical cohesion types, emancipation